Why and how to improve the subdivision technique in mass metrology. (December 2021) - Zelenka, Z.; Alisic, S.; Hanrahan, R.; Kolozinsky, I.; Popa, G.; Zůda, J.; Malengo, A.
Abstract: Subdivision is an indispensable technique in mass metrology because it allows the determination of the mass of weights of various nominal values and the realisation of the mass scale. After the redefinition of the kilogram, this technique is becoming more important since the realisation of the kilogram now contributes a greater uncertainty than before. This means that the reference mass standard used to calibrate a set of weights has higher uncertainty (the previous definition of the kilogram had zero uncertainty), which increases the uncertainty of all the weights. A rigorous analysis is set about investigating whether this seriously affects the measurement capabilities, and if it does, how it can be compensated. Project 19RPT02, "Improvement of the realisation of the mass scale" (EMPIR [1] Call 2019 –Research Potential), has been, among others, dedicated to this problem, and some of the findings are presented here.